2022
DOI: 10.1002/jcsm.12936
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability in response to protein and fish oil supplementation in older adults: a randomized controlled trial

Abstract: Background Precision nutrition is highly topical. However, no studies have explored the interindividual variability in response to nutrition interventions for sarcopenia. The purpose of this study was to determine the magnitude of interindividual variability in response to two nutrition supplementation interventions for sarcopenia and metabolic health, after accounting for sources of variability not attributable to supplementation. Methods A 24 week, randomized, double‐blind, placebo‐controlled trial tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Of all studies, 4 were 2-arm RCTs ( Table 3 ). The mean age of the study participants was between 63 and 77.4 years [ 9 34 35 36 ]. As studies have investigated the effect of omega-3 fatty acids in combination with other ingredients or foods (e.g., fruit juice), the control group for intervention in these studies corresponded to a formula or food without omega-3 fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all studies, 4 were 2-arm RCTs ( Table 3 ). The mean age of the study participants was between 63 and 77.4 years [ 9 34 35 36 ]. As studies have investigated the effect of omega-3 fatty acids in combination with other ingredients or foods (e.g., fruit juice), the control group for intervention in these studies corresponded to a formula or food without omega-3 fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…While most studies utilizing protein supplementation with omega-3 are beneficial, one study reported no significant effects of EPA and DHA on skeletal muscle mass and strength. The study was conducted in a manner similar to the aforementioned studies with older adults aged ≥ 65 years [ 35 ] and defined sarcopenia or low handgrip strength according to the European Working Group on Sarcopenia in Older People 2010 (EWGSOP1) criteria [ 1 ]. A 10.6 g whey protein and 3.1 g of total leucine, or protein with omega-3 fatty acids containing 0.8 g EPA and 1.1 g DHA were supplied to the participants for 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches have been implemented in some recent interesting original studies regarding the effect of an endurance training protocol on various muscle and whole-body adaptations, 26 the impact of sprint interval exercise training on fasting and postprandial insulin sensitivity adaptations, 27 and the effect of protein and fish oil supplementation on biochemical, morphological and functional characteristics in older adults. 29 For the aims of the present study, we designed a two-treatment, two-period AB/BA crossover design. 41 We assessed potential carry-over effects as previously suggested, 42 data was analyzed using a linear mixed-effects model, 17 and individual probabilities of response along with the population proportions of response were also calculated.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate inter‐individual variability in the responses after a nutritional intervention within the context of exercise physiology and sports nutrition. Similar approaches have been implemented in some recent interesting original studies regarding the effect of an endurance training protocol on various muscle and whole‐body adaptations, 26 the impact of sprint interval exercise training on fasting and postprandial insulin sensitivity adaptations, 27 and the effect of protein and fish oil supplementation on biochemical, morphological and functional characteristics in older adults 29 . For the aims of the present study, we designed a two‐treatment, two‐period AB/BA crossover design 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation